Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12896-019-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Copy number determination of the gene for the human pancreatic polypeptide receptor NPY4R using read depth analysis and droplet digital PCR

Abstract: Background Copy number variation (CNV) plays an important role in human genetic diversity and has been associated with multiple complex disorders. Here we investigate a CNV on chromosome 10q11.22 that spans NPY4R , the gene for the appetite-regulating pancreatic polypeptide receptor Y4. This genomic region has been challenging to map due to multiple repeated elements and its precise organization has not yet been resolved. Previous studies using microarrays were interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Here we assessed the prevalence of protein truncating variants (PTV: stop gain, frameshift and splice variants) in genes previously associated with NPD as well as CNVs in regions previously implicated in NPD. We undertook further studies to assess the prevalence of CNVs in two other cohorts with microarray data: a cohort of patients referred for obesity management to University College London Hospital, London UK (UCLH cohort) comprising patients with EO and less extreme obesity (O, BMI [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and a Swedish cohort of participants with predominantly O recruited from the community.…”
Section: Introductionmentioning
confidence: 99%
“…Here we assessed the prevalence of protein truncating variants (PTV: stop gain, frameshift and splice variants) in genes previously associated with NPD as well as CNVs in regions previously implicated in NPD. We undertook further studies to assess the prevalence of CNVs in two other cohorts with microarray data: a cohort of patients referred for obesity management to University College London Hospital, London UK (UCLH cohort) comprising patients with EO and less extreme obesity (O, BMI [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] and a Swedish cohort of participants with predominantly O recruited from the community.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies in which this method is used for the determination of copy number variation is increasing, 32,[34][35][36][37]41,42 since copy number values are calculated in an absolute way directly by the software, without the need of standard samples for normalization. Data obtained from the present study are in keeping with those observed by Sallustio et al, 37 as a higher stability in KIV2 repeats measurement is achieved with ddPCR in comparison to that observed with qPCR technique.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…ddPCR is rapidly gaining in popularity over standard real-time PCR assays for its relative ease of use, precise and accurate results, and ability to quantify nucleic acid concentration without the need for standard samples. 31,32 The number of publications in which this technology is employed for the investigation of CNVs, which can impact from single genes to regions of larger size, such as chromosomal rearrangements, continues to grow, [33][34][35][36][37][38] progressively opening up new avenues for the use of ddPCR in diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Amplicon lengths of SNP assays were 93, 70, 95, 67, 85 and 75 bp, respectively. RPP30 (amplicon length of 62 bp) and RPPH1 (amplicon length of 135 bp) assays were described previously (Oscorbin et al, 2019; Shebanits et al, 2019). RPPH1 and RPP30 were selected because they are single copy genes per haploid human genome and are commonly used as reference genes in copy number variation studies (Imaizumi et al, 2019; Oscorbin et al, 2019; Shebanits et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…RPP30 (amplicon length of 62 bp) and RPPH1 (amplicon length of 135 bp) assays were described previously (Oscorbin et al, 2019; Shebanits et al, 2019). RPPH1 and RPP30 were selected because they are single copy genes per haploid human genome and are commonly used as reference genes in copy number variation studies (Imaizumi et al, 2019; Oscorbin et al, 2019; Shebanits et al, 2019). SRY assay for quantification of presence of chromosome Y was designed as follows: forward primer 5’-CGAAGTGCAACTGGACAACAG-3’, reverse primer 5’-TAGCTGGTGCTCCATTCTTGAG-3’ and probe 5’-ACAGGGATGACTGTACGAAAGCCACACA-3’ (HEX, ZEN-3IABkFQ) (Integrated DNA Technologies), with amplicon length of 76 bp.…”
Section: Methodsmentioning
confidence: 99%